The COVID-19 CARES Act: What should be done for U.S. farms? - Smith, Vincent H.; Glauber, Joseph W. (Real Clear, 2020)
Like other businesses, farmers and ranchers are facing short-run adverse effects of the COVID-19 crisis and longer-term recession challenges. One important difference is that farming is considered an essential activity, and unlike many service businesses, farms are not being asked to shut down their operations. Despite this, Congress has included in the CARES Act bailout an additional $23.5 billion for the agricultural sector. Ensuring that these funds are targeted to farm households in need should be a priority.